Trajectories of Cognitive Decline in Brain Donors With Autopsy-Confirmed Alzheimer Disease and Cerebrovascular Disease. (14th June 2022) - Frank, Brandon; Ally, Madeline; Tripodis, Yorghos; Puzo, Christian; Labriolo, Caroline; Hurley, Landon; Martin, Brett; Palmisano, Joseph; Chan, Lawrence; Steinberg, Eric; Turk, Katherine; Budson, Andrew; et al.
Abstract : Background and Objectives: Cerebrovascular disease (CBVD) is frequently comorbid with autopsy-confirmed Alzheimer disease (AD), but its contribution to the clinical presentation of AD remains unclear. We leveraged the National Alzheimer's Coordinating Center (NACC) uniform and neuropathology datasets to compare the cognitive and functional trajectories of AD+/CBVD+ and AD+/CBVD− brain donors. Methods: The sample included NACC brain donors with autopsy-confirmed AD (Braak stage ≥3, Consortium to Establish a Registry for Alzheimer's Disease score ≥2) and complete Uniform Data Set (UDS) evaluations between 2005 and 2019, with the most recent UDS evaluation within 2 years of autopsy. CBVD was defined as moderate to severe arteriosclerosis or atherosclerosis. We used propensity score weighting to isolate the effects of comorbid AD and CBVD. This method improved the balance of covariates between the AD+/CBVD+ and AD+/CBVD− groups. Longitudinal mixed-effects models were assessed with robust bayesian estimation. UDS neuropsychological test and the Clinical Dementia Rating Scale Sum of Boxes (CDR-SB) scores were primary outcomes. Results: Of 2, 423 brain donors, 1, 476 were classified as AD+/CBVD+. Compared with AD+/CVBD− donors, the AD+/CBVD+ group had accelerated decline (i.e., group × time effects) on measures of processing speed (β = −0.93, 95% CI −1.35, −0.51, Bayes factor [BF] 130.75), working memory (β = 0.05, 95% CI 0.02, 0.07, BF 3.59), verbal fluency (β = 0.10, 95% CI 0.04, 0.15, BF 1.28), naming (β = 0.09, 95% CI 0.03, 0.16, BF = 0.69), and CDR-SB (β = −0.08, 95% CI −0.12, −0.05, BF 18.11). Effects ranged from weak (BFs <3.0) to strong (BFs <150). We also found worse performance in the AD+/CBVD+ group across time on naming (β = −1.04, 95% CI −1.83, −0.25, BF 2.52) and verbal fluency (β = −0.73, 95% CI −1.30, −0.15, BF 1.34) and more impaired CDR-SB scores (β = 0.45, 95% CI 0.01, 0.89, BF 0.33). Discussion: In brain donors with autopsy-confirmed AD, comorbid CBVD was associated with an accelerated functional and cognitive decline, particularly on neuropsychological tests of attention, psychomotor speed, and working memory. CBVD magnified effects of AD neuropathology on semantic-related neuropsychological tasks. Findings support a prominent additive and more subtle synergistic effect for comorbid CBVD neuropathology in AD.